Carbon‐Bridged p‐Phenylenevinylene Polymer for High‐Performance Solution‐Processed Distributed Feedback Lasers. Issue 13 (10th April 2018) - Morales‐Vidal, Marta; Quintana, José A.; Villalvilla, José M.; Boj, Pedro G.; Nishioka, Hiroki; Tsuji, Hayato; Nakamura, Eiichi; Whitworth, Guy L.; Turnbull, Graham A.; Samuel, Ifor D. W.; Díaz‐García, María A.
Abstract: Thin‐film organic lasers are attractive light sources for a variety of applications. Recently, it is reported that carbon‐bridged oligo( p ‐phenylenevinylene)s (COPV n with repeating unit n = 1–6) function as unique laser dyes which combine high fluorescence efficiency, wavelength tunability, and both thermal and photostability, making them ideal for use in organic semiconductor lasers. However, in order to obtain such excellent properties, COPV n require blending in a matrix, such as a thermoplastic polymer, thus leading to miscibility issues, limited absorption, and charge transporting properties. Here, high‐performance lasers with a novel active polymer poly‐COPV1, based on the basic unit of COPV1 and prepared as a high‐quality neat film, are reported which overcome the trade‐off between the device performance and durability. The prepared lasers show thresholds 30 times lower and operational lifetimes 300 times longer than devices based on COPV1 dispersed in polystyrene. The low threshold operation allows the poly‐COPV1 lasers to be pumped by a nitride diode laser. Abstract : High‐performance solution‐processed distributed feedback lasers based on a carbon‐bridged p ‐phenylenevinylene polymer are reported. The lasers, with neat films of a novel active polymer poly‐COPV1, based on the basic unit of COPV1, show thresholds 30 times lower and operational lifetimes 300 times longer than devices based on COPV1 dispersed in polystyrene.